IMPLEMENTASI METODE PEMBELAJARAN PPT BERBASIS GAME TERHADAP PRESTASI AKADEMIK DAN MOTIVASI SISWA BIMBEL KAMPUNG SABI - Kurniawati Martha; Murniwati Gulo; Yohanes Edi Gunanto; Henni Sitompul; Maya Puspitasari Izaak (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Alpha Tutoring (bimbel) is a community service program to help children in Sabi Village understand Mathematics and Science lessons. Many students experience learning difficulties due to economic constraints, lack of supervision at home, and less than ideal school conditions such as frequent empty periods due to teacher absences. These conditions lead to low learning motivation and student understanding of the material. This program aims to provide additional lessons with a fun, game-based approach. This program also serves as a means for Teachers College students to develop teaching skills in the community. This activity is held twice a week, namely on Mondays for Mathematics and Thursdays for Science, starting from September 19, 2024 - May 26, 2025. The methods used are lectures, discussions, questions and answers, and the use of game strategies containing material and questions using PPT media. The purpose of the strategy game with PPT is to check student understanding in a fun way. Based on a questionnaire completed by 41 students, data obtained 85% stated that they were very happy to participate in tutoring. Regarding student learning motivation, data obtained 88% of students were very motivated to use this method. 63% of students found it significantly helpful because they understood the material better. This demonstrates that game-based learning methods can increase motivation and improve student learning outcomes.